Ali je ustna pogodba o prodaji poslovnega deleža veljavna - Čarni, Martin (Podjetje in delo, 2023)
The article deals with share purchase agreements as legal transactions binding the parties to perform certain obligations (titulus iuris) from the viewpoint of formality requirements for their validity. In dealing with the aforementioned issue, the article tries to confirm the hypothesis that the applicable regulations do not set forth a special requirement regarding the form of share purchase agreements as legal transactions binding the parties, which, consequently, means that verbally (or even implicitly) concluded share purchase agreements are validly concluded. The article deals with the aforementioned issues by first examining the applicable legal regulations and the existing caselaw in the relevant areas. The article further compares the regulation in the area of legal transactions with business shares with the regulation in the area of legal transactions with real property, and then compares the Slovenian regulation of legal transactions with business shares with the German and Austrian regulations in this area. At the end, the paper also answers certain arguments that appear in the caselaw regarding the required formality of share purchase agreements as legal transactions binding the parties, whereby providing further arguments in support of the article's research hypothesis.
Keywords: družbe z omejeno odgovornostjo; gospodarsko pravo; notarski zapis; obličnost; pogodbe; poslovni delež; pravni posel